BANTUAN DESAIN FONDASI MINIPILE MASJID KAPAL MUNZALAN BANJARBARU - Yusti Yudiawati; Joni Irawan; Akhmad Marzuki; Ahmad Norhadi (LP2M Universitas Hasanuddin, 2024)
Munzalan Ship Mosque in Banjarbaru is one of the branches of many Munzalan Ship Mosques which is found in various cities in Indonesia. This mosque is planned to have a four-story structure shaped similar to a ship and purple colored. The absence of experts in conducting soil investigations and foundation designing is the motivation for providing related services which will be used to fulfill one of the requirements for Building Approval (PBG) and Functional Conditions (SLF) by the Banjarbaru Government. The soil investigation was conducted in the form of a Cone Penetration Test (CPT) at 2 (two) locations, where the hard soil layer was found at a depth of 17 – 18 meters, so the foundation used was planned to be a rectangular minipile foundation with the dimension of 25 cm x 25 cm and a depth of 18 meters. The planned single pile load capacity is 255.48 tons and 291.54 tons. The resulting foundation requirements are 1 (one) pile at 11 joints, 2 (two) piles at 18 joints, and 3 (three) piles at 9 joints. Control calculations of the axial force of the structure show that the number of planned piles can support the load of the structure above it with SF > 1. Foundation design planning assistance facilitates the process of obtaining an optimal and efficient minipile foundation design. The surrounding community, management, and construction committee of the Kapal Munzalan Mosque gained knowledge and understanding of the building foundation design process. — Masjid Kapal Munzalan Banjarbaru merupakan cabang dari Masjid Kapal Munzalan yang terdapat di berbagai kota di Indonesia. Masjid ini direncanakaan memiliki struktur setinggi empat lantai berbentuk menyerupai kapal dan bernuansa warna ungu. Tidak adanya tenaga ahli dalam pelaksanaan penyelidikan tanah dan perencanaan fondasi menjadi motivasi dalam memberikan pengabdian berupa penyelidikan tanah dan perencanaan fondasi yang akan digunakan untuk memenuhi salah satu persyaratan Persetujuan Bangunan Gedung (PBG) dan Syarat Layak Fungsi (SLF) oleh pihak Kota Banjarbaru. Penyelidikan tanah berupa Cone Penetration Test (CPT)/Sondir pada 2 (dua) titik dengan lapisan tanah keras pada kedalaman 17 m – 18 m. Direncanakan menggunakan minipile 25 cm x 25 cm sedalam 18 m. Diperoleh daya dukung tiang tunggal rencana sebesar 255,48 ton dan 291,54 ton. Dihasilkan kebutuhan fondasi tiang sebanyak 1 (satu) buah tiang pada 11 joint, 2 (dua) buah tiang pada 18 joint, dan 3 (tiga) buah tiang pada 9 joint. Perhitungan kontrol terhadap gaya aksial struktur menunjukkan jumlah tiang rencana mampu menopang beban struktur di atasnya denagn SF > 1. Bantuan perencanaan desain pondasi memperlancar proses mendapatkan desain fondasi minipile yang optimal dan efisien. Masyarakat sekitar, Pengurus dan Panitia Pembangunan Masjid Kapal Munzalan mendapatkan pengetahuan dan pemahaman proses desain fondasi bangunan.